2015
DOI: 10.1021/acs.nanolett.5b00648
|View full text |Cite
|
Sign up to set email alerts
|

Quality Heterostructures from Two-Dimensional Crystals Unstable in Air by Their Assembly in Inert Atmosphere

Abstract: Many layered materials can be cleaved down to individual atomic planes, similar to graphene, but only a small minority of them are stable under ambient conditions. The rest react and decompose in air, which has severely hindered their investigation and potential applications. Here we introduce a remedial approach based on cleavage, transfer, alignment, and encapsulation of air-sensitive crystals, all inside a controlled inert atmosphere. To illustrate the technology, we choose two archetypal two-dimensional cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
522
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(550 citation statements)
references
References 47 publications
21
522
3
4
Order By: Relevance
“…Блок и из подобных ста-бильных 2D-кристаллов будут служить, по мне-нию исследователей, стандартными гетеро-структурами для различных устройств, в том числе, возможно, и легких батарей для мобиль-ного аккумулирования энергии [11]. В допол-нение к этим элементам во Франции изготов-лены асимметричный нанобарьер (молекула) и #3 / 65 / 2016 combination of chemically dissimilar atoms or two-dimensional single crystals, the energy levels of the outer electrons which differ by a significant amount.…”
Section: Nanotechnology For Electric Powerunclassified
See 1 more Smart Citation
“…Блок и из подобных ста-бильных 2D-кристаллов будут служить, по мне-нию исследователей, стандартными гетеро-структурами для различных устройств, в том числе, возможно, и легких батарей для мобиль-ного аккумулирования энергии [11]. В допол-нение к этим элементам во Франции изготов-лены асимметричный нанобарьер (молекула) и #3 / 65 / 2016 combination of chemically dissimilar atoms or two-dimensional single crystals, the energy levels of the outer electrons which differ by a significant amount.…”
Section: Nanotechnology For Electric Powerunclassified
“…Games under the guidance of R. Gorbacheva inert gas obtained is stable in the air, layers upon layers of 2D materials. Blocks of these stable 2D crystals will serve, according to the researchers, the standard heterostructures for various devices, including, perhaps, light batteries for mobile energy storage [11]. In addition to these items made in France asymmetric nanoseries (molecule) and nanoampere [12].…”
Section: Nanotechnology For Electric Powermentioning
confidence: 99%
“…Various quasi-two-dimensional (2d) materials are known to exhibit a competition of superconducting (SC), charge density wave, and magnetic phases [1][2][3][4][5][6][7][8][9][10][11] , with notably different dependences of the resulting phase diagrams on the number of layers. While in some systems, such as the Fe-based superconductors, the highest transition temperatures T c are reached in the monolayer limit (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of negative compressibility have been previously observed in ultraclean systems, such as in high-quality LaAlO 3 /SrTiO 3 interfaces [9], two-dimensional (2D) GaAs systems [4,[10][11][12], and ferroelectric materials [13], where Coulomb interactions are normally strong and play an important role in transport properties. Newly emerged 2D layered semiconductors, such as transition-metal dichalcogenides [14][15][16][17][18] and black phosphorus (BP) [19][20][21][22][23][24][25][26][27][28], are new platforms for both nanotechnology and fundamental physics. Among these 2D materials, atomically thin BP is a promising channel material of FETs with high mobility [24][25][26][27] and high stability by encapsulating BP with hexagonal boron nitride (BN) sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Newly emerged 2D layered semiconductors, such as transition-metal dichalcogenides [14][15][16][17][18] and black phosphorus (BP) [19][20][21][22][23][24][25][26][27][28], are new platforms for both nanotechnology and fundamental physics. Among these 2D materials, atomically thin BP is a promising channel material of FETs with high mobility [24][25][26][27] and high stability by encapsulating BP with hexagonal boron nitride (BN) sheets. Our previous work has found that high-quality BN-BP-BN heterostructures with clean interfaces are ideal 2D electron systems with high mobility [25].…”
Section: Introductionmentioning
confidence: 99%